Analysis of the Provisión Fondo de Innovación para la Competitividad: foundation, operation and improvement spaces (Revista LIDER, 2020)
Chile's economic development model has been characterized by being mainly based on the exploitation of commodities (primarily from the mining and agricultural sectors).From it, between the years 1990 and 1999, an average growth rate of 6.4% was obtained (despite the recession caused by the Asian crisis), however, between 2000 and 2010, that growth reached only 3.8% on average.This situation, according to various diagnoses, reflects a depletion of the aforementioned model, which has resulted in the need to introduce changes in it. In this context, the Innovation Fund for Competitiveness is created in 2006, in order to focus resources to promote the generation of an economy based on knowledge with a source of diversification and sophistication.Then, in 2008, the provision of the Innovation Fund for the Competitiveness ofregional allocation was created, giving its administration to the regional governments with the purpose of supporting territorial economic development through regional innovation and improving its competitiveness.In this regard, there are several criticisms regarding the fulfillment of its objectives, the results obtained and the way in which its allocation operates, which become more important in a context of the need to improve productivity and demands for greater decentralization, being the Fiscal scope one of the most relevant.It is for this reason that this work seeks, from the review of literature related toscience, technology and innovation policies, as well as the descriptive analysis of databases on the distribution and allocation of the FIC and the application of a survey of perception regarding its justification and operation, to detect antecedents that are useful for evaluating the performance of this provision and make recommendations that evaluate its improvement within the topics indicated. Based on the above, proposals will be made in relation to the policies and operation of the FIC provision, which will be useful to support the work carried out by SUBDERE in this area.